One-pot efficient synthesis of β-aryl-β-sulfanyl ketones via a four-component reaction of alkyl halides, thiourea benzaldehydes and acetophenones. Issue 9 (27th February 2020) - Abbasi, Mohammad; Nowrouzi, Najmeh; Mousavi, Saadat
Graphical abstract: Highlights: The first one-pot four-component synthesis of β-aryl-β-sulfanyl ketones. Simple reactants including alkyl halides, thiourea, benzaldehydes and acetophenones. Free of unpleasant thiol smell. Simple methodology, high yields, appropriate reaction times and green solvent. Abstract: A one-pot efficient synthesis of β-aryl-β-sulfanyl ketones is introduced via a tandem aldol condensation-thia-Michael addition process using NaOH in the poly ethylene glycol (PEG-200). Addition of different thiols in situ generated from the reaction of alkyl halides with thiourea to chalcones, formed in situ from the condensation of acetophenone derivatives with benzaldehydes, led to a high yielding synthesis of the products.